2008
DOI: 10.1016/j.jtcvs.2008.06.028
|View full text |Cite
|
Sign up to set email alerts
|

The transapical approach for aortic valve implantation

Abstract: Initial results of the transapical approach are encouraging. Long-term studies and randomized protocols will be required to further evaluate this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 21 publications
1
55
0
2
Order By: Relevance
“…The reported rate of surgical interventions due to bleeding following TAVI by a transapical approach is 8-14% [42][43][44]. Development of LV pseudoaneu rysm is another very rare but severe complication in patients treated using a transapical approach [45].…”
Section: Complications Of Tavi Proceduresmentioning
confidence: 99%
“…The reported rate of surgical interventions due to bleeding following TAVI by a transapical approach is 8-14% [42][43][44]. Development of LV pseudoaneu rysm is another very rare but severe complication in patients treated using a transapical approach [45].…”
Section: Complications Of Tavi Proceduresmentioning
confidence: 99%
“…However, definitions are sometimes heterogeneous and must be considered carefully when outcomes from multiple studies are combined. In the case of TAVI, 30-day mortality is generally favorable and ranges from 0% to 25% (Behan et al, 2008;Berry et al, 2007;Cribier et al, 2002;De Jaegere et al, 2008;Descoutures et al, 2008;Grube et al, 2006;Grube et al, 2007;Piazza et al, 2008;Rodes-Cabau et al, 2008;Spargias et al, 2008;Svensson et al, 2008;Tamburino et al, 2009;Walther et al, 2007;Walther et al, 2008;Webb et al, 2007;Ye et al, 2009;Zierer et al, 2008). Thirty-day mortality rates appear to be similar between the different devices and between transapical and transfemoral access routes.…”
Section: Safety Of Tavimentioning
confidence: 99%
“…Only Edwards Lifesciences devices are currently licensed for use using the transapical approach. Ye et al (2009) and Zierer et al (2008) both reported success rates of 100% in small case series using transapical access. In larger studies the success rates are similarly impressive.…”
Section: Feasibility Of Tavimentioning
confidence: 99%
See 1 more Smart Citation
“…Czę-stość interwencji chirurgicznej u chorych po zabiegu TAVI z dostępu TAA z powodu krwawienia wynosiła 8-14% [19][20][21]. Innym, bardzo rzadkim, ale ciężkim powikłaniem u pacjentów po TAA jest wytworzenie się tętniaka rzekomego lewej komory serca [22].…”
Section: Powikłania Związane Z Przezcewnikową Implantacją Zastawki Aounclassified